2021
DOI: 10.1155/2021/6638915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miRNA-140 on the Growth and Clinical Prognosis of SMMC-7721 Hepatocellular Carcinoma Cell Line

Abstract: Background. A growing number of studies have suggested that microRNAs exert an essential role in the development and occurrence of multiple tumours and act as crucial regulators in various biological processes. However, the expression and function of miRNA-140 in hepatocellular carcinoma (HCC) cells are not yet adequately identified and manifested. Methods. The expression of miRNA-140 was determined in HCC tissues and adjacent nontumour tissues by quantitative real-time polymerase chain reaction (qRT-PCR). Kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…With the development of molecular biology, the detection of biomarkers can provide an effective assessment of the prognosis of LC. e expression of miRNA is related to the growth, proliferation, migration, and other processes of tumor cells and affects the occurrence and prognosis of many diseases including tumors [22][23][24]. Many studies are limited to the clinical analysis of patients with SP and LC, while ignoring the importance of clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of molecular biology, the detection of biomarkers can provide an effective assessment of the prognosis of LC. e expression of miRNA is related to the growth, proliferation, migration, and other processes of tumor cells and affects the occurrence and prognosis of many diseases including tumors [22][23][24]. Many studies are limited to the clinical analysis of patients with SP and LC, while ignoring the importance of clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Various researches indicated that abnormal expression of lncRNAs is highly correlated to the prognosis and metastasis of HCC [ 5 , 6 ]. MicroRNA (miRNA) is a class of endogenous, single-stranded, non-coding RNAs of 19–25 nt length [ 7 ], in which its prominent role is to bind to the 3’ untranslated region of its target mRNA, thereby inhibiting gene expression [ 8 ]. The interactions of mRNA, miRNA, and lncRNA play multiple roles in the development of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…HCC cell lines are powerful tools. Until now, ten human HCC cell lines have been established, and every cell line has its own characteristics and offers convenience for various experiments [16][17][18][19]. Stability, homogeneity and straightforward culture are important parameters permanently in cell lines.…”
Section: Medicinal Plantmentioning
confidence: 99%